2010
DOI: 10.1021/jp1054759
|View full text |Cite
|
Sign up to set email alerts
|

Physical Adsorption of Charged Plastic Nanoparticles Affects Algal Photosynthesis

Abstract: The physical adsorption of nanosized plastic beads onto a model cellulose film and two living algal species, Chlorella and Scenedesmus, has been studied. This adsorption has been found to ubiquitously favor positively charged over negatively charged plastic beads due to the electrostatic attraction between the beads and the cellulose constituent of the model and living systems. Such a charge preference is especially pronounced for Chlorella and Scenedesmus, whose binding with the plastic beads also depended up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
374
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(404 citation statements)
references
References 23 publications
20
374
3
7
Order By: Relevance
“…199.3 ± 176.3 nm (range 100-500 nm) after 28 days, using TEM. Bhattacharya et al (2010) measured substantial binding or heteroaggregation of 20 nm polystyrene particles with freshwater phytoplankton cells. Because of their low density, it is often assumed that substantial fractions of the total load of plastic particles from riverine sources reach the sea (Cózar et al 2014;Wagner et al 2014).…”
Section: Fate Of Nanoplasticmentioning
confidence: 98%
See 2 more Smart Citations
“…199.3 ± 176.3 nm (range 100-500 nm) after 28 days, using TEM. Bhattacharya et al (2010) measured substantial binding or heteroaggregation of 20 nm polystyrene particles with freshwater phytoplankton cells. Because of their low density, it is often assumed that substantial fractions of the total load of plastic particles from riverine sources reach the sea (Cózar et al 2014;Wagner et al 2014).…”
Section: Fate Of Nanoplasticmentioning
confidence: 98%
“…This study used an air-inhalation exposure scenario and the question remains to what extent this can be translated to aquatic systems, where aggregation would limit the concentrations of free NPs and direct inhalation of air-dispersed NPs does not occur. Bhattacharya et al (2010) showed that adsorption of 1.8-6.5 mg/L of 20 nm polystyrene particles (yet present as agglomerates) hindered algal photosynthesis, possibly through reduction of light intensity and of air flow by the nanoparticles, and stimulated Reactive Oxygen Species (ROS) production. Ward and Kach (2009) showed that mussels (Mytilus edulis) and oysters (Crassostrea virginica) take up 100 nm PS beads, especially when incorporated into aggregates.…”
Section: Bioaccumulation and Effects Of Nanoplasticsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Similarly, in the algae Chlorella and Scenedesmus, polystyrene microbeads have been shown to generate ROS and inhibit photosynthetic ability. 18 Despite growing concern regarding the deleterious effects of microplastics on marine organisms, particularly on filter feeding plankton at the bottom of the food chain, the defense mechanisms of marine organisms in response to microplastic ingestion have not yet been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, in open coasts, wave action may transfer a large portion of the marine debris from shallow areas to the shore [2]. Marine pollution leads to: • Nanopolystyrene beads can inhibit photosynthesis and cause oxidative stress in algae [26].…”
Section: Litter Transfer Accumulation and Effectsmentioning
confidence: 99%